Formulasi dan Evaluasi Sediaan Granul Effervescent Ekstrak Kulit Buah Sukun (Artocarpus altilis) - Djamal Julia Megawati; Muh Hidayat; Miftahurrahmah Pansariang (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Breadfruit (Artocarpus altilis) is a kind of consumable plant, generally peoples will process the fruit and discharge the peel. Effervescent granule is a practice of powder preparation. This study aim to create the effervescent granulation preparation to making the peel if breadfruit will easier to consumen with extract concentrations : F1 (5%), F2 (10%), and F3 (15%) and determine the characteristics of the resulting preparation. Making effervescent granules using the alkaline granulation method. Then the resulting preparation is evaluated by testing, including organoleptic test, pH, flow rate, angle of repose, dissolve time, water content, granule size distribution, and froth height. Breadfruit peel extract can be formulated into effervescent granule preparations. Effervescent granules of F1, F2, and F3 from breadfruit peel extract produce a brownish-white powder, characteristic of the extract. All of the formulas have qualified pH, water content, rest angle, dissolve time, and granule size. Flow velocity F1 7.99 g/sec and F2 7.21 g/sec, including flow velocity